Answer: a) -13/16
Step-by-step explanation: Start by setting equations equal and rearrange X^3 - x^2 + 1 = 0. Visual inspection of graph shows x between -1 and -1/2. Start with x = 3/4 plug in and calculate: just a little too small. Try going halfway towards -1: x =-7/8 Plug in and the answer is very far from 0. Go halfway back towards -3/4: -13/16 and the equality is very close.
Answer:
B
Step-by-step explanation:
Answer:
(x, y) = (- 3, 4)
Step-by-step explanation:
Given the 2 equations
5x + 2y = - 7 → (1)
4x - y = - 16 → (2)
multiply all terms in (2) by 2
8x - 2y = - 32 → (3)
Add (1) and (3) term by term
(5x + 8x) + (2y - 2y) = (- 7 - 32)
13x = - 39 ( divide both sides by 13 )
x = - 3
Substitute x = - 3 into either (1) or (2) and solve for y
substituting in (1) gives
(5 × - 3) + 2y = - 7
- 15 + 2y = - 7 ( add 15 to both sides )
2y = 8 ( divide both sides by 2 )
y = 4
solution is (- 3, 4 )
(4,-1)
These are the only numbers that weren’t repeated yet.
11. x² - 7x = 0
x(x) - x(7) = 0
x(x - 7) = 0
x = 0 or x - 7 = 0
+ 7 + 7
x = 7
Solution Set: {0, 7}
12. 3x² - 4x = 20x + 27
+ 4x + 4x
3x² = 24x + 27
3x² - 24x - 27 = 0
x = -(-24) ± √((-24)² - 4(3)(-27))
2(3)
x = 24 ± √(576 + 324)
6
x = 24 ± √(900)
6
x = 24 ± 30
6
x = 4 ± 5
x = 4 + 5 or x = 4 - 5
x = 9 or x = -1
Solution Set: {9, -1}